(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
The purpose of this study is to investigate the effects of benefit-sharing arrangements in the resettlement of the Mangla Dam Raising Hydropower Project, focusing on the processes by which the resettlement planning and execution were carried out. Additionally, the study aims to identify the challenges and nature of the benefit-sharing programs provided in the MDRP resettlement. A qualitative approach was employed to explore the perceptions of local communities and to identify the direct and indirect benefits of this project’s implementation. The study was conducted in New Mirpur City, where a significant number of people were affected by the project. A purposive sampling method was used to select participants. Through in-depth semi-structured interviews, incorporating local and demographic contexts, the research found that while some individuals benefited from the project by comparing their new lifestyle, many did not receive adequate compensation and continued to express grievances. The results indicate that the expectations of widespread satisfaction among the affected people were not met, and it was also revealed that the newly settled area remains underdeveloped with significant unfinished work. The findings highlight a need for more transparent and inclusive benefit-sharing mechanisms in large-scale resettlement projects. Furthermore, the study underscores the importance of addressing the long-term socio-economic impacts on the resettled communities to ensure sustainable development.